O futebol como estratégia de ascensão na sociedade de risco: o atleta "sem clube" e sua identidade - Leme, Clodoaldo Gonçalves (2011)
The main purpose of this thesis is to understand the professional identity of a group of Brazilian soccer players - persons who choosed this career as a way to social progress, were excluded from professional sport and now are unemployed. The study attempts to establish fundaments to extend theoretical proposal on the issue of identity as a metamorphosis in seeking emancipation. The study also brings ideas on profession and training of this group of soccer players individuals that literally got out of the game , failing in his goals. Having as background the Critical Social Psychology, the research tries to look soccer in its social aspects, in connection with theories and approaches that provide foundations that enable a critical reading of the world s most popular sport.Valuing life stories, we examine some situations that pervade the lives of our group of soccer players. The study follows up describing a scenario constructed to highlight the importance of Social Psychology approach, exploring the concept of identity and life stories analysis as a way of producing knowledge.Further, it presents a panorama from life stories brought, as well as other analytical elements that link the main situations that soccer players face when they are excluded from the soccer market. This study provides, therefore, a vision of training, socialization and individuation of our target-group; It identifies how structural issues, ideological orientations, and social institutions are bound by the personalities of soccer players soccer stars , normal ones , and losers